2015
DOI: 10.1113/jphysiol.2014.280404
|View full text |Cite
|
Sign up to set email alerts
|

The impact of arterial load on left ventricular performance: an invasive haemodynamic study in severe mitral stenosis

Abstract: Key pointsr A hallmark of mitral stenosis (MS) is the markedly altered left ventricular (LV) loading. r As most of the methods used to determine LV performance in MS patients are influenced by loading conditions, previous studies have shown conflicting results.r The present study calculated LV elastance, which is a robust method to quantify LV function.We demonstrate that LV loading in MS patients is elevated but normalizes after valve repair and might be a result of reflex pathways.r Additionally, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In this study, increased LV chamber stiffness normalized after balloon intervention 6 . Other mechanisms proposed to explain reduced LV compliance in MS include restriction of regional myocardial segments 13 and the influence of a dilated, overloaded right heart on left‐sided distensibility 19,38 . Negative diastolic pressures have been demonstrated in MS which characterizes ventricular early diastolic suction 34 .…”
Section: Invasive Evaluationmentioning
confidence: 53%
See 1 more Smart Citation
“…In this study, increased LV chamber stiffness normalized after balloon intervention 6 . Other mechanisms proposed to explain reduced LV compliance in MS include restriction of regional myocardial segments 13 and the influence of a dilated, overloaded right heart on left‐sided distensibility 19,38 . Negative diastolic pressures have been demonstrated in MS which characterizes ventricular early diastolic suction 34 .…”
Section: Invasive Evaluationmentioning
confidence: 53%
“…In the 1950s, studies by Harvey 1 and Fleming 2 explored mechanistic theories related to the presentation of depressed LV function in MS. Surgical commissurotomy was widely considered as an effective therapy to relieve symptoms at that time, and the ability to distinguish patients with mechanical obstruction that may benefit from surgery from those with primary myocardial insufficiency held clinical and prognostic relevance. Several studies have subsequently reported reduced pump performance in this setting 3‐8 and have attributed this to variable mechanisms that include impaired LV filling secondary to mitral valvular obstruction, 9‐11 chronic myocardial inflammation, 12‐14 sub‐valvular scarring resulting in regional abnormalities, 3,15,16 elevated systemic load, 4,17‐19 and right–left interactions 20 (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an index of left ventricular (LV) function has been developed using a noninvasive estimation of myocardial elastance that allows an investigator to assess the elastic potential energy of the heart (7). This index is well correlated with invasive measures of myocardial contractility and has been adopted for clinical assessments of LV function (38,40,52). Along with noninvasive LV pressure and volume estimations, it can be used to generate noninvasive pressure volume relationships, which might provide a less variable index of total mechanical energy than RPP.…”
Section: Coronary Blood Flow In Humans Is Responsive To Both Changes mentioning
confidence: 99%
“…Reduced C v has been attributed to a functional restriction related to the thickened immobile valve apparatus tethered to the ventricular chamber rather than a permanent myocardial abnormality . Therefore, PMV sufficiently improves valve apparatus mobility to release this constraining effect on the ventricle, thereby revealing relatively normal underlying myocardial chamber properties …”
Section: Discussionmentioning
confidence: 99%
“…Reduced C v has been attributed to a functional restriction related to the thickened immobile valve apparatus tethered to the ventricular chamber rather than a permanent myocardial abnormality. 27,28 Therefore, PMV sufficiently improves valve apparatus mobility to release this constraining effect on the ventricle, thereby revealing relatively normal underlying myocardial chamber properties. 27 Previous studies addressing the impact of atrial compliance on pulmonary artery pressure have used net atrioventricular compliance (C n ), derived by Doppler echocardiography, 29 which is comparable to invasively measured C av .…”
Section: Effects Of Pmv On Left Chamber Compliancementioning
confidence: 99%